2018
DOI: 10.1002/joc.5950
|View full text |Cite
|
Sign up to set email alerts
|

Bias nonstationarity of global climate model outputs: The role of internal climate variability and climate model sensitivity

Abstract: Bias correction methods are developed based on the assumption that the biases of climate model outputs are stationary, that is, the characteristics of the bias are constant over time. However, recent studies have shown the biases are not always stationary. The objectives of this study are to investigate the impacts of bias nonstationarity of climate-model-simulated precipitation and temperature on future climate projections, and the roles of internal climate variability (ICV) and climate model sensitivity (CMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…For example, Ahmadalipour et al, (2017) ranked 20 GCMs based on their skills in simulating multiple aspects of daily observations in Columbia River Basin, which could provide an objective reference for selecting more reliable GCMs for regional climate change impact assessment. However, the ranks of GCMs may be altered due to their nonstationary performances in simulating climates (Hui et al, 2019). Another type of approaches seeks to preserve the uncertainty of climate change signals related to the choice of GCMs (Cannon, 2015; Warszawski et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ahmadalipour et al, (2017) ranked 20 GCMs based on their skills in simulating multiple aspects of daily observations in Columbia River Basin, which could provide an objective reference for selecting more reliable GCMs for regional climate change impact assessment. However, the ranks of GCMs may be altered due to their nonstationary performances in simulating climates (Hui et al, 2019). Another type of approaches seeks to preserve the uncertainty of climate change signals related to the choice of GCMs (Cannon, 2015; Warszawski et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This may be because the bias of intervariable correlation simulated by climate models is not stationary, and the observed intervariable correlation itself is also not invariable. Previous studies (Chen et al, 2017; Hui et al, 2018; Maraun, 2012) have shown that bias correction methods can deteriorate the original climate simulations when bias directions are different between future and historical periods (or calibration and validation periods) or when future biases reduce to less than half the calibration biases. The nonstationarity of intervariable correlation bias of climate models can be observed in Figure S7.…”
Section: Discussionmentioning
confidence: 99%
“…Climate model precipitation biases are not always stationary. Internal climate variability is a substantial source of such bias nonstationarity (Hui et al, ). It was ignored in most climate change impact studies, which resulted in large underestimation of uncertainty.…”
Section: Discussionmentioning
confidence: 99%